Pemanfaatan Minyak Jelantah untuk Produksi Sabun: Solusi Inovatif untuk Pengurangan Limbah dan Ekonomi Sirkular - Fridayani, Helen Dian; Darumurti, Awang; Mutmainah, Nur Fitri; Mawaddah, Habliy; Widyasari, Sindy (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2025)
Background: Improper disposal can lead to severe pollution, contaminating soil and water sources. To address this issue, a community service program was launched in Selopamioro Village to educate residents on reusing used cooking oil into more beneficial products, such as soap. Beyond its environmental benefits, the program also aims to enhance participants' skills and entrepreneurial abilities, providing a sustainable source of income. Method: The program engaged 30 youths and 35 housewives and was structured in three phases: (1) an awareness campaign to highlight the environmental and economic benefits of reusing used cooking oil, (2) hands-on soap-making training that guided participants step by step and (3) an evaluation phase to assess the program's effectiveness and gather feedback. Result: This program has shown a positive impact by increasing environmental awareness and practical skills among participants. The high level of enthusiasm and positive feedback reflect the program’s successful implementation. It effectively empowered the community, particularly women, through soap-making training using used cooking oil, which not only created income opportunities but also fostered environmental responsibility. The program contributed to reducing household waste and supported local economic growth. Its success demonstrates strong potential for replication in other communities. Conclusion: Continued support in business management, marketing, and product innovation is essential to ensure the program’s sustainability.